Comparison of Compliance of Different Iron Chelators Including Original and Bioequivalents of Deferasirox - Aksu, Tekin; Özbek, Namık Yaşar; Söker, Murat; Coşkun, Çağrı; Güzelküçük, Zeliha; Üzel, Hülya Veysiye; Yaralı, Neşe; Gümrük, Fatma; Ünal, Şule (Acta Medica, 2020)
Objective: The current iron chelation therapy regimens include deferoxamine (DFO), deferiprone (DFP), and deferasirox (DFX) in transfusion-dependent patients. Compliance with iron-chelating therapy is one of the significant determinants of mortality and morbidities related to iron loading in chronically transfused patients. This survey aims to compare the compliance and the satisfaction of DFO, DFP, and DFX formulations in patients who have iron-overloading in three hematology centers from Turkey. Moreover, bioequivalent (generic) formulations of dispersible DFX tablet compared with the original formulation in terms of taste and treatment compliance. Patients and Methods: A written questionnaire with a list of pre-set questions was applied to measure patient-reported outcomes to a total of 85 patients, where 77 had beta-thalassemia major, 7 had beta-thalassemia intermedia, and 1 had sickle cell anemia diagnoses. Results: The patients’ median age at enrollment was 15 years (range 7 – 42). The compliance was below 50% in 8 (18.6%), 4 (16%), and 5 (6.7%) in patients receiving DFO, DFP, and DFX, respectively. Additionally the compliance was below 80% in 16 (37.2%), 9 (36%), and 17 (22.6%) in patients receiving DFO, DFP, and DFX, respectively. It was found that 39 (47%) patients had compliance problems due to the dispersible DFX tablet formulations’ taste, except combination therapies. There was no difference between the currently used oral chelators in terms of taste and treatment compliance. Conclusion: This study draws attention to compliance problems in patients with iron-loading anemias, partly due to the unpleasant taste of DFX. Improving patient satisfaction and compliance with iron-chelator therapy may reduce complications of iron overload.